Small protease inhibitors in tick saliva and salivary glands and their role in tick-host-pathogen interactions - Martins, Larissa Almeida; Kotál, Jan; Bensaoud, Chaima; Chmelař, Jindřich; Kotsyfakis, Michail (Biochimica et biophysica acta. Proteins and proteomics, 2020)
Ticks must durably suppress vertebrate host responses (hemostasis, inflammation, immunity) to avoid rejection and act as vectors of many pathogenic microorganisms that cause disease in humans and animals. Transcriptomics and proteomics studies have been used to study tick-host-pathogen interactions and have facilitated the systematic characterization of salivary composition and molecular dynamics throughout tick feeding. Tick saliva contains a complement of protease inhibitors that are differentially produced during feeding, many of which inhibit blood coagulation, platelet aggregation, vasodilation, and immunity. Here we focus on two major groups of protease inhibitors, the small molecular weight Kunitz inhibitors and cystatins. We discuss their role in tick-host-pathogen interactions, how they mediate the interaction between ticks and their hosts, and how they might be exploited both by pathogens to invade hosts and as candidates for the treatment of various human pathologies.
Keywords: Animals; slinné žlázy; aprotinin; Aprotinin; Salivary Glands; Protease Inhibitors; sliny; Host-Parasite Interactions; proteomika; inhibitory proteas; interakce hostitele a parazita; Cystatins; Proteomics; klíšťata; Ticks; Saliva; transkriptom; zvířata; Transcriptome; cystatiny